PENGARUH DIGITAL MARKETING DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA ERA EKONOMI DIGITAL - Ali Syah Putra (MTU PRESS, 2025)
The advancement of digital technology has changed how businesses market to their customers. One of the primary strategies for raising brand awareness and influencing customer purchase decisions is now digital marketing. The purpose of this study is to examine how brand recognition and digital marketing affect customer purchasing decisions. Customers who actively utilize digital media are given surveys to complete as part of the quantitative research method. Regression analysis was used to examine the gathered data in order to ascertain the correlation between the variables under investigation. The findings demonstrate that brand recognition and customer purchasing decisions are positively and significantly impacted by digital marketing. Furthermore, it has been demonstrated that brand awareness has a significant impact on purchasing decisions. It is anticipated that this study would help businesses create more successful digital marketing plans to boost their competitiveness in the age of the digital economy.